Differential effects of ibuprofen and indomethacin on cerebral oxygen kinetics in the very preterm baby - Stark, Michael J.; Crawford, Tara M.; Ziegler, Nina M.; Hall, Anthea; Andersen, Chad C. (Frontiers in Pediatrics, 2022)
Background: Ibuprofen is preferred to indomethacin for treatment of a significant patent ductus arteriosus (PDA) in preterm babies despite indomethacin being associated with a lower risk of intraventricular haemorrhage. While differential effects on cerebral oxygen kinetics is proposed as the underlying mechanism, the effect of ibuprofen on cerebral perfusion and oxygenation is still debated. Methods: Forty-eight babies <30 weeks with a significant PDA, defined by echocardiography, were randomly assigned to either indomethacin or ibuprofen (n=24 per group) and stratified by gestation and chronologic age. Cerebral blood flow (total internal carotid blood flow (TICF)) and oxygen physiology (oxygen delivery (modCerbDO2) and consumption (modCerbVO2) were measured, and cerebral oxygen extraction (cFTOE)) calculated immediately before and following administration using cranial Doppler ultrasound and near-infrared spectroscopy. Temporal and treatment related changes were analysed. Results: A fixed effect of time was seen for TICF (p=0.03), modCerbDO2 (p=0.046) and calculated FTOE (p=0.04) for indomethacin alone. In the indomethacin group TICF and modCerbDO2 fell from baseline to 5- and 30-mins respectively (TICF p<0.01, cDO2 p=0.01) before increasing from 5 min to 24-hour (p<0.01) and 30 min and 24-hour (p<0.01) timepoints. Calculated cFTOE peaked at 30 minutes (p=0.02) returning to baseline at 24 hours. There was a parallel increase in arterial lactate. Conclusions: Indomethacin significantly reduces cerebral blood flow resulting in a parallel increase in oxygen extraction and arterial lactate. This implies that the balance of oxygen consumption and delivery at the time of treatment may be critical in very preterm babies with PDA.